The narcissism of minor resemblances: searching for allies at times of threat - Drožđek, Boris (Frontiers in Psychology, 2024)
Humans must identify others as enemies or allies to develop, protect, maintain, and refine their sense of self. This is a part of their normal psychological development. These phenomena operate on individual and large group levels and are pronounced under threat. In peril, they help create psychological boundaries between conflicting parties and bonds between allies. These boundaries and bonds are invested with strong emotions. The narcissism of minor differences concept is involved in identifying and delineating enemies at times of perceived danger. This article introduces the concept of the narcissism of minor resemblances. This concept is discussed from the psychodynamic perspective and illustrated with examples of socio-political developments from modern history. The narcissism of minor resemblances concept may help us understand the underlying dynamics of bonding with allies and identifying with others when undergoing threat and hardship. This concept connects the public arena of political action with individual psychological development. Awareness of this phenomenon can help mitigate the negative aspects of rigid enemy-ally distinctions and promote cooperation and peace. It may also help individuals impacted by psychological trauma to make meaning of psychological and societal processes experienced and contribute to their healing.